Citizen perceptions and interactions towards self-sufficiency, community plot ratio and civic generosity within sustainable neighbourhoods - Joseph Llewellyn; Cecilia Katzeff; Daniel Pargman; Fredrik Johansson (City and Environment Interactions)
The United Nations Environment Programme (UNEP) released design indexes for sustainable neighbourhoods, including self-sufficiency, community plot ratio and civic generosity. However, they are developed from an urban planning perspective and not researched in relation to: a) the citizen perspective and b) how citizen interactions can contribute to the environment. Therefore, this research tests a novel set of indexes with an underused method of ethnographic video interviews with 14 citizens of a known sustainable neighbourhood in Stockholm, Sweden. A thematic analysis conducted on 28 h of interview data collected over a 4-week period yielded 5 main themes, from outdoor public spaces. Self-sufficiency findings suggest that citizens 1) perceive small scale self-sufficiency to be challenged by large scale structural efficiency and 2) circular actions with food waste to biogas can develop the self-sufficiency index further. Community plot ratio findings suggest that citizens 3) perceive community spaces to be accessible for all but not used by all. Civic generosity findings suggest citizens 4) perceive an imbalance between self-interests of the individual versus collective interests of the community, while 5) experienced citizens feel personally responsible to pioneer civic generosity interactions. UNEP indexes for designing neighbourhoods can define local sustainability, however, our findings support this, only if they can be acted upon by the citizens who live there.